2021
DOI: 10.1186/s12879-021-06934-7
|View full text |Cite
|
Sign up to set email alerts
|

The microbiological diagnostic performance of metagenomic next-generation sequencing in patients with sepsis

Abstract: Background In this study, we aimed to perform a comprehensive analysis on the metagenomic next-generation sequencing for the etiological diagnosis of septic patients, and further to establish optimal read values for detecting common pathogens. Methods In this single-center retrospective study, septic patients who underwent pathogen detection by both microbial culture and metagenomic next-generation sequencing in the intensive care unit of the S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 18 publications
(25 reference statements)
1
21
0
Order By: Relevance
“…Our findings suggested that the mNGS can identify multiple pathogens in clinical specimens including blood, wound secretion, BALF, ascites, and sputum from septic patients and shows evidently higher positive rates than diagnostics based on standard microbiological blood cultures in terms of timely and accurately determining etiological pathogens for suspected and confirmed cases of sepsis due to well-performed data interpretation. These benefits were also reported in previously reported studies [ 35 , 36 ], which suggested that mNGS confers a valuable diagnostic platform for determining relevant pathogens mNGS is broadly applied for detecting pathogens and especially for the timely and accurate diagnosis of critical illness including sepsis due to suspected etiology microbes [ 37 , 38 ]. Previous evidence has proved the application of mNGS in identifying various viruses via samples of nasopharyngeal swabs, serum, or solid tissue [ 39 , 40 ], as well as in identification of bacteria from urine, vaginal swabs, or sputum [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 69%
“…Our findings suggested that the mNGS can identify multiple pathogens in clinical specimens including blood, wound secretion, BALF, ascites, and sputum from septic patients and shows evidently higher positive rates than diagnostics based on standard microbiological blood cultures in terms of timely and accurately determining etiological pathogens for suspected and confirmed cases of sepsis due to well-performed data interpretation. These benefits were also reported in previously reported studies [ 35 , 36 ], which suggested that mNGS confers a valuable diagnostic platform for determining relevant pathogens mNGS is broadly applied for detecting pathogens and especially for the timely and accurate diagnosis of critical illness including sepsis due to suspected etiology microbes [ 37 , 38 ]. Previous evidence has proved the application of mNGS in identifying various viruses via samples of nasopharyngeal swabs, serum, or solid tissue [ 39 , 40 ], as well as in identification of bacteria from urine, vaginal swabs, or sputum [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 69%
“…Hence, distinguishing causative microbes from background microbiota is a crucial challenge in interpreting mNGS data. Although the read values of mNGS are commonly used for the interpretation of distinct pathogenic infections ( 33 35 ), the cutoff reads for diagnosing distinct microbes using mNGS and their clinical significance remain to be clarified. However, in cases of polymicrobial infections, while predominant pathogens are detected, less abundant pathogens may be filtered out by high detection thresholds.…”
Section: Discussionmentioning
confidence: 99%
“…With broad coverage, fast detection speed, and high accuracy, mNGS represents a new, less biased approach that can detect thousands to millions of nucleotides fragments at once ( 20 ). Compared to other traditional genetic diagnostic methods, such as PCR, mNGS can detect a wide range of hard-to-culture, atypical and rare pathogens without prior target knowledge ( 21 ). However, the relatively high cost, complicated procedure and strict protocol for preventing specimen contamination limit the wider application of NGS, which requires a professional and well-trained laboratory team.…”
Section: Discussionmentioning
confidence: 99%